An Optimized Lock Solution Containing Micafungin, Ethanol and Doxycycline Inhibits Candida albicans and Mixed C. albicans - Staphyloccoccus aureus Biofilms. - Livia Lown (PLoS ONE, 2016)
Candida albicans is a major cause of catheter-related bloodstream infections and is associated with high morbidity and mortality. Due to the propensity of C. albicans to form drug-resistant biofilms, the current standard of care includes catheter removal; however, reinsertion may be technically challenging or risky. Prolonged exposure of an antifungal lock solution within the catheter in conjunction with systemic therapy has been experimentally attempted for catheter salvage. Previously, we demonstrated excellent in vitro activity of micafungin, ethanol, and high-dose doxycycline as single agents for prevention and treatment of C. albicans biofilms. Thus, we sought to investigate optimal combinations of micafungin, ethanol, and/or doxycycline as a lock solution. We performed two- and three-drug checkerboard assays to determine the in vitro activity of pairwise or three agents in combination for prevention or treatment of C. albicans biofilms. Optimal lock solutions were tested for activity against C. albicans clinical isolates, reference strains and polymicrobial C. albicans-S. aureus biofilms. A solution containing 20% (v/v) ethanol, 0.01565 μg/mL micafungin, and 800 μg/mL doxycycline demonstrated a reduction of 98% metabolic activity and no fungal regrowth when used to prevent fungal biofilm formation; however there was no advantage over 20% ethanol alone. This solution was also successful in inhibiting the regrowth of C. albicans from mature polymicrobial biofilms, although it was not fully bactericidal. Solutions containing 5% ethanol with low concentrations of micafungin and doxycycline demonstrated synergistic activity when used to prevent monomicrobial C. albicans biofilm formation. A combined solution of micafungin, ethanol and doxycycline is highly effective for the prevention of C. albicans biofilm formation but did not demonstrate an advantage over 20% ethanol alone in these studies.